Effect of Intermediate Principal Stress on Cylindrical Tunnel in an Elasto-plastic Rock Mass. (2017) - Singh, Aditya; Rao, K. Seshagiri; Ayothiraman, Ramanathan
Abstract: In the present study, theoretical solutions are presented for the prediction of stresses around a cylindrical tunnel using several failure criteria such as Mogi–Coulomb, Inscribe Drucker-Prager, Middle Circumscribe Drucker-Prager, Circumscribe Drucker-Prager and Mohr-Coulomb failure criteria in an elasto-plastic rock mass. For the analysis, details of a typical tunnel and rock mass properties in Himalayan region were considered. The plastic zone around the circular tunnel which requires support system was quantified from the results of theoretical solutions for each criterion separately. It is observed that the stresses and thickness of plastic zone predicted by Inscribe Drucker-Prager and Middle Circumscribe Drucker-Prager criteria were very close to Mohr-Coulomb criterion. It is noticed that the Circumscribe Drucker-Prager Criterion predicts the smallest plastic zone among other criteria, since this criterion overestimates the strength of material compared to experimentally measured strength. But it is inferred that Mogi-Coulomb Criterion which predicts the material strength with good accuracy. The plastic zone predicted by Mogi- Coulomb is about 20% lesser than that was predicted by Mohr-Coulomb failure criteria. This indicates that consideration of effect of intermediate principal stress with an appropriate failure criterion could lead an economical design of tunnel support system.